Coping with salt stress-interaction of halotolerant bacteria in crop plants: A mini review - Ramasamy, Kesava Priyan; Mahawar, Lovely (Frontiers in Microbiology, 2023)
Salinity is one of the major environmental abiotic stress factors that limit the growth and yield of crop plants worldwide. It is crucial to understand the importance of several adaptive mechanisms in plants toward salt stress so as to increase agricultural productivity. Plant resilience toward salinity stress is improved by cohabiting with diverse microorganisms, especially bacteria. In the last few decades, increasing attention of researchers has focused on bacterial communities for promoting plant growth and fitness. The biotechnological applications of salt-tolerant plant growth-promoting rhizobacteria (PGPR) gained widespread interest for their numerous metabolites. This review provides novel insights into the importance of halotolerant (HT) bacteria associated with crop plants in enhancing plant tolerance toward salinity stress. Furthermore, the present review highlights several challenges of using HT-PGPR in the agricultural field and possible solutions to overcome those challenges for sustainable agriculture development in the future.